Initial Understanding of Increasing National Spirit Through Project Based Learning on the Story of the Nation’s Struggle in Madrasah Ibtidaiyah - Lisa Nurfadila Ningsi; Nurzakiah Simangunsong (Journal of Contemporary Islamic Primary Education, 2025)
This study aims to explore how Project-Based Learning (PjBL) based on the nation's struggle stories can enhance the spirit of nationalism among students at Madrasah Ibtidaiyah (MI) in Kendari City. The main issue addressed is how to integrate the teaching of national struggle history to foster a sense of nationalism among young learners. This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews with teachers and students, classroom observations, and documentation of learning products. The data analysis technique used is thematic analysis, with data validity ensured through source triangulation. The findings show that the implementation of PjBL based on national struggle stories significantly improves students' understanding of national history and strengthens their sense of nationalism. Through active involvement in projects such as creating models and documentary videos, students feel more connected to national values. As a result, they demonstrate improved national character, a greater sense of pride in Indonesia’s history, and a stronger spirit of unity. This research provides important implications for curriculum development and experience-based teaching methodologies that emphasize national values in primary education.